TAHLIL MADAT ALQIRAAT FI KITAB ALLUGHAT ALEARABIAT LILSAFI ALTHAALITH ALMUTAWASIT EAM 2020 MIN WIZARAT ALSHUWUWN ALDIYNIAT ALIINDUNISIA - Ach. Tabrani; Adam Dimyati; Rizal Firdaus (Program Studi Pendidikan Bahasa Arab, 2024)
The research dealt with the texts of the reading subject in the Arabic language book for the third intermediate grade and its related rules. This is based on the observation of the researcher who discovered a lack of consistency between the sentence structures included in the reading subject and the structures studied in the grammar subject. The research aimed to identify the suitability of those texts contained in the reading subject and the rules accompanying them, and to come up with structural proposals in order to modify the researched book. The research followed the descriptive approach, using observation as well as qualitative analysis methods in processing the research data. The research reached two results, the first of which is that the reading material in the Arabic language textbook for the third intermediate grade in 2020 AD is not grammatically appropriate. Some of the texts included in the reading subject did not cover the most important topics explained in the grammar subject. The second is that the writing of educational books and the preparation of their materials must be based on psychological, cultural, educational and linguistic foundations, consistent with their cognitive, skill and emotional objectives, achieving the principles of harmony, progression and balance, and taking into account the desires of the learners and the individual differences between them